The Impact of Project-Based Learning on Collaborative and Critical Thinking Skills of Students in Translation Course - Tambunan, Elissa Evawani; Ramadhani, Yulia Rizki; Sibuea, Bismar (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
This study investigates the effectiveness of project-based learning (PjBL) in translation education, focusing on the development of students' collaborative and critical thinking skills. Using a quasi-experimental design, the research examines how engagement in real-world translation projects influences students' active learning, integration of theory and practice, and overall engagement in the learning process. Key findings indicate that PjBL significantly increases student participation, fosters the application of theoretical knowledge in practical settings, and improves essential professional skills such as teamwork and decision-making. The research contributes to the field of translation learning by highlighting the potential of PjBL as an innovative and effective teaching strategy. It emphasizes the importance of designing and implementing project-based activities that enrich students' learning experiences and prepare them for the complexities of professional translation work. However, the study acknowledges certain limitations, including its limited focus on a single educational context, which may affect the generalizability of the findings. Future research directions are suggested, including exploring the impact of PjBL in different educational settings and assessing its long-term effects on students' career readiness and professional development.